Formação profissional e prática docente: uma análise do ensino desenvolvido por professores de Biologia e Química do município de Itacoatiara – AM - Sampaio, Lissandra Santana (Brasil, 2022)
Training and teaching practice are objects of study from a very early age, since knowing educators and their role in the teaching process implies knowing the challenges of this practice. In this perspective, the present work aims to analyze the profile and professional performance of high school teachers of the disciplines of Biology and Chemistry from 12 state schools in the municipality of Itacoatiara - AM. For this, the methodology had a quantitative - qualitative approach of descriptive character, with the application of an online questionnaire, containing open and closed questions. It was observed with the results that the majority of the public of participating teachers is in the age group between 26 and 40 years old, characterizing a young group, where all of them have higher education, with 48% being graduates of the Licentiate in Sciences: Chemistry and biology and 69% have a postgraduate degree. It was also found that many of the teachers more often use strategies and resources characterized by traditional teaching, such as lectures and textbooks. In addition, the results obtained show that 34% of the teachers considered the students' adherence to the remote teaching format as bad or very bad, as well as, in the report of these professionals, access to the internet and technological resources was one of the great challenges for them. teaching during the pandemic. We conclude that, in view of the results, it is necessary to carry out more research in the area, which can deepen the theme, as well as understand the aspects present in educational institutions that limit the performance of the teaching professional.